Monetisasi Dan Rasionalisasi Konsumsi Pada Wacana Lipstick Effect Dalam Promosi Merek The Originote - Lintang Arum Bagasati; Sari, Mutia Novela; Syahnaz Savitri (Jurnal Ilmu Komunikasi, 2026)
This study examines The Originote brand’s promotional strategies, which represent the monetization and rationalization of consumer emotions through the Lipstick Effect phenomenon. This phenomenon illustrates consumers’ tendency to purchase products even under limited economic conditions. The study employs Fairclough’s Critical Discourse Analysis with three levels of analysis: text, discursive practice, and social practice. Data were collected purposively from promotional content on The Originote’s TikTok account (@theoriginote) between January and October 2025 to capture emerging discourse patterns. The findings show that, at the textual level, narratives of affordability, social closeness, and humor are used to frame consumption as a logical and emotional form of self-care. At the discursive practice level, content is adjusted to specific moments, reflecting sensitivity to consumers’ emotional states and life rhythms. At the social practice level, affective capitalism operates by framing consumption as a form of personal responsibility while simultaneously reproducing gendered pressures to appear attractive. The promotional discourse shapes consumer mindsets through language that combines economic, symbolic, and affective functions, aligning with the logic of the Lipstick Effect.